Development of human resource management system for Barangay Mintal, Davao City - Atay, Sefrey Dickson Magtuba (2009)
Human Resource Management System for Barangay Mintal, Davao City (HRMS Min) is an online human resource management system for the barangay. It allows users to keep records of residents of the barangay and execute processes of the barangay. The system has four types of users. First is the administrator that creates barangay accounts and user accounts for a specific barangay. Second are the read and write users that are responsible in populating residents? data in the system and perform the recording of processes made in the barangay. These processes include registration of residents, recording of complaints, issuing barangay clearance with a document file (.doc extension), uploading and organizing files, creating reports. Third re the read only users that can view detailed information on the records of the barangay. The read only user cannot change any record in the barangay, their main role is to observe and supervise the barangay from the data suggested by the system. The fourth user is the general public or the common user; their user is the one that visits the website to gather information from the main page of the system. Information that can be gathered in the main page are: list of the barangay. The system can provide assistance to barangay processes and also promote tourist spots to foreign and local viewers
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2009
Keywords: Compatibility study; Compiler invocation; Examination maker; Online examinations; Online examination systems; Human resource management system; Human resource management system -- Mintal, Davao City -- Philippines